A recombined allele of the lipase gene CEL and its pseudogene CELP confers susceptibility to chronic pancreatitis - Fjeld, Karianne; Bugert, Peter (Nature genetics, 2015)
Carboxyl ester lipase is a digestive pancreatic enzyme encoded by the CEL gene1. Mutations in CEL cause maturity-onset diabetes of the young as well as pancreatic exocrine dysfunction2. Here we describe a hybrid allele (CEL-HYB) originating from a crossover between CEL and its neighboring pseudogene, CELP. In a discovery series of familial chronic pancreatitis cases, we observed CEL-HYB in 14.1% (10/71) of cases compared to 1.0% (5/478) of controls (odds ratio (OR) = 15.5; 95% confidence interval (CI) = 5.1-46.9; P = 1.3 × 10-6 by two-tailed Fisher's exact test). In three replication studies of nonalcoholic chronic pancreatitis, we identified CEL-HYB in a total of 3.7% (42/1,122) cases and 0.7% (30/4,152) controls (OR = 5.2; 95% CI = 3.2-8.5; P = 1.2 × 10-11; formal meta-analysis). The allele was also enriched in alcoholic chronic pancreatitis. Expression of CEL-HYB in cellular models showed reduced lipolytic activity, impaired secretion, prominent intracellular accumulation and induced autophagy. These findings implicate a new pathway distinct from the protease-antiprotease system of pancreatic acinar cells in chronic pancreatitis.
Gesehen am 30.11.2017